Spatial distribution of weed, nematode, and Western corn rootworm egg populations in corn fields - Wyse-Pester, Dawn Y., author; Westra, Philip, advisor; Wiles, Lori J., committee member; Hoeting, Jennifer, committee member; Peairs, Frank B., committee member (Colorado State University. Libraries, 2000)
Knowing the distribution of pests in farmer-managed fields could help researchers develop reliable distribution maps that could be used for site-specific pest management. Two com fields (71 and 53 ha) in eastern Colorado were sampled in 1997 and 1998 to investigate the spatial distribution of weed, plant-parasitic nematode, and western com rootworm egg populations. Weed seedlings or mature plants were observed when com reached the two-leaf, four-leaf, and physiological maturity stages. Weedy plants were observed on a 76.2 m square grid, a random-directed grid where sites were established at intervals of 76.2 m, and star configurations based on a 7.62 m grid within three 23223 m2 areas. Pigweed seeds collected on the 76.2 m square and 7.62 m star grids were screened for triazine-resistance. Nematodes and rootworm eggs were sampled at all 76.2 m square grid sites prior to com harvest each year. Spearman rank correlation was calculated for densities of nematode, rootworm egg, and triazine-resistant pigweed distributions with soil attributes of organic matter, sand, silt, and clay. Directional correlograms were calculated for 0, 30, 60, 90, 120, and 150 degrees from the crop row for weeds and calculated for 0, 45, 90, and 135 degrees for nematodes and rootworm eggs. Clay was positively correlated with resistant pigweed seedbank populations in both years. Seven of 93 weed density distributions were spatially correlated up to 5 to 363 m. Spiral and stunt nematode densities were correlated with sand, silt, clay, and organic matter and 3 of 12 density distributions for spiral and lesion nematode densities were spatially correlated up to 97 to 845 m. Rootworm egg densities were not correlated to soil attributes but 1 of 4 distributions was spatially correlated up to 69 to 76 m. Due to the minimal detection of spatial correlation for weed seedling, nematode, or rootworm egg distributions in eastern Colorado com fields, interpolated density maps should not be created from a 7.62 m grid for weed seedling infestations or a 76.2 m grid for nematode or rootworm egg infestations.
Keywords: agronomy